Impact of Climate Change on Soil Erosion - Raudha Anggraini Tarigan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2022)
Global warming is expected to result in a more vigorous hydrological cycle, including total rainfall and more frequent high-intensity rainfall events, which affect soil erosion and cause a threat to agricultural land sustainability and productivity, particularly in tropical and subtropical regions. This study aims to determine the effects of climate change on soil erosion in Taiwan. This experiment assesses the risk of soil erosion in Taiwan over 2 – 200 years. To determine the predictor of soil erosion risk, the study used USPED. Result showed there was an increase in sediment yield because of soil erosion. Hence, targeting conservation practices to erosion-prone areas, expanding conservation coverage, and adapting agronomic practices may be necessary to prevent excessive soil erosion under climate change scenarios that include intensified precipitation.